Method for stripping MoSe2 nanosheet based on liquid phase of pyridine ionic liquid aqueous solution
By using pyridine ionic liquids with specific alkyl chain lengths as intercalating agents, ultrasonic liquid-phase exfoliation of MoSe2 nanosheets was achieved, solving the problems of low exfoliation efficiency and low yield of MoSe2 nanosheets in existing technologies, and realizing the large-scale preparation of few-layer MoSe2 nanosheets at high efficiency and low cost.
Patent Information
- Application Number
- CN202511205773.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-12-02
AI Technical Summary
Existing liquid-phase exfoliation methods for MoSe2 nanosheets suffer from problems such as the use of toxic organic solvents, low exfoliation efficiency, low yield, and difficulty in controlling the number of layers, which cannot meet the needs of large-scale production.
Pyridine ionic liquids with specific alkyl chain lengths are used as intercalating agents to exfoliate MoSe2 nanosheets via ultrasonic liquid phase. The Lewis acid-base interaction between the alkyl chains and anions in the pyridine ionic liquid and the MoSe2 layers expands the interlayer spacing and weakens van der Waals forces, thus achieving efficient exfoliation.
We have achieved high-quality, low-cost, and large-scale preparation of few-layer MoSe2 nanosheets with a yield of up to 37%, and the proportion of nanosheets with a thickness of less than 2 nm is as high as 80%, which is environmentally friendly and controllable.
Smart Images

Figure CN121044547A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-efficiency liquid-phase exfoliation technology for MoSe2 nanosheets, specifically relating to a method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution. Background Technology
[0002] MoSe2 is a type of transition metal chalcogenide compound with the general chemical formula MX2, where M represents transition metal atoms from groups IVB to VIII (such as Ti, Mo, W, Zr, Nb, Ta, etc.), and X represents chalcogenides such as S, Se, or Te. These materials possess a unique "sandwich" layered structure: the top and bottom layers are planar structures formed by chalcogenides (X) through covalent bonds, with a middle layer formed by transition metal atoms (M), and the layers interact through weak van der Waals forces. Due to its atomic-level thickness, tunable band gap, and high carrier mobility, MoSe2 shows broad application prospects in flexible electronic devices, nanoelectronics and optoelectronic devices, photocatalysis (such as solar water splitting), energy storage (such as lithium-sulfur batteries), and biosensing. However, the poor solubility and processability of bulk MoSe2 greatly limit its further applications. In contrast, MoSe2 nanosheets, due to the exposure of more active sites, exhibit better dispersion stability in solvents, further expanding its application areas. Currently, strategies for preparing MoSe2 nanosheets mainly fall into two categories: bottom-up and top-down approaches. Bottom-up methods involve chemically reacting precursors of reactants under specific conditions to generate two-dimensional thin film materials, including chemical vapor deposition (CVD) and wet chemical synthesis methods (such as hydrothermal methods). Top-down methods use external forces (such as ultrasound or shear force) to exfoliate bulk materials into single-layer or few-layer nanosheets, such as liquid-phase exfoliation and mechanical exfoliation. Liquid-phase exfoliation is considered a simple, low-cost, and large-scale method for preparing nanosheets; however, its practical application has revealed a series of critical problems that urgently need to be solved. For example, the solvents used for MoSe2 liquid-phase exfoliation are often toxic organic solvents with high boiling points that are difficult to remove; simultaneously, the yield of MoSe2 nanosheets prepared by this method is low, failing to meet the needs of large-scale production, and it performs poorly in terms of layer number control, making it difficult to accurately obtain MoSe2 nanosheets with a specific number of layers. Therefore, it is necessary to develop a controllable exfoliation strategy based on an environmentally friendly solvent system to achieve efficient preparation of high-quality MoSe2 nanosheets (target number of layers 1-3, yield >30%).
[0003] Existing patent document CN201611244941.5 discloses a liquid-phase exfoliation method for preparing two-dimensional black phosphorus nanosheets. The method involves adding bulk black phosphorus and a nitrogen-containing ionic liquid at a mass ratio of 1:0.5–100 to an organic solvent to obtain a mixture. Under anaerobic conditions at 0–10°C, the mixture is first subjected to probe sonication for 3–7 hours, followed by water bath sonication for 1–10 hours, and then allowed to stand. The supernatant is then centrifuged to obtain two-dimensional black phosphorus nanosheets. This method achieves efficient exfoliation of bulk black phosphorus into large-sized porous two-dimensional black phosphorus nanosheets through the synergistic effect of the nitrogen-containing ionic liquid and the organic solvent. Although this patent discloses a method for liquid-phase ultrasonic exfoliation of two-dimensional black phosphorus nanosheets using ionic liquids, it employs the synergistic use of ionic liquids and organic solvents, and does not describe the use of a specific pyridine-based ionic liquid aqueous solution for liquid-phase exfoliation of MoSe2 nanosheets.
[0004] Existing patent document CN201710295717.7 discloses a method for liquid-phase exfoliation of transition metal disulfide nanosheets. In this method, a small-molecule aqueous solution containing phosphate is mixed with a solid powder of transition metal disulfide at room temperature. After ultrasonication for 30 hours, the mixture is centrifuged for 20 minutes to remove the precipitate; the supernatant is then removed by centrifugation. The precipitate is redispersed to obtain a dispersion of transition metal disulfide nanosheets, wherein the dispersant is water. The transition metal disulfide nanosheets are MoS2, WS2, MoSe2, or WSe2 nanosheets. This patented technology avoids the use of highly hazardous organolithium compounds and environmentally harmful toxic organic solvents required for the preparation of transition metal disulfide nanosheets in existing methods. However, its liquid-phase exfoliation process uses a small-molecule aqueous solution containing phosphate, resulting in a relatively low exfoliation yield and a long ultrasonic exfoliation time. Furthermore, there is no record of using a specific pyridine-based ionic liquid aqueous solution for liquid-phase exfoliation of MoSe2 nanosheets. Summary of the Invention
[0005] The technical problem solved by this invention is to provide a simple, low-cost, large-scale, high-quality, and efficient method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquids in aqueous solution. This method uses pyridine-based ionic liquids with specific alkyl chain lengths to perform liquid-phase exfoliation of bulk MoSe2 materials. The pyridine-based ionic liquid acts as an intercalating agent, increasing the interlayer spacing of the bulk material through the length of the alkyl chain, thereby weakening the interlayer interaction forces and promoting exfoliation. Furthermore, the C=OO ratio of the anions in the pyridine-based ionic liquid... - Lewis acid-base interactions exist between the functional groups and the bulk MoSe2 layers. This interaction drives pyridine ionic liquids to enter the MoSe2 interlayer, effectively weakening the interlayer van der Waals forces and facilitating liquid-phase exfoliation. This, in turn, effectively improves the exfoliation efficiency of the bulk MoSe2 and the yield of MoSe2 nanosheets.
[0006] To solve the above-mentioned technical problems, this invention adopts the following technical solution: a method for liquid-phase exfoliation of MoSe2 nanosheets based on an aqueous solution of a pyridine-based ionic liquid. The specific steps are as follows: MoSe2 bulk material is placed in an aqueous solution of a pyridine-based ionic liquid for ultrasonic liquid-phase exfoliation using a probe; the dispersion is then centrifuged, washed, and dried to obtain MoSe2 nanosheets. The pyridine-based ionic liquid is 1-dodecylpyridineisonicotinic acid [C]. 12 [py][C6H5NO2], 1-Tetradecylpyridineisonicotinic acid [C 14 [py][C6H5NO2] or 1-hexadecylpyridineisonicotinic acid [C 16 [py][C6H5NO2];
[0007] The structural formula of the anion in the pyridine-based ionic liquid is:
[0008]
[0009] The structural formula of the cation in the pyridine-based ionic liquid is:
[0010]
[0011] Further specifying, the feeding ratio of the block material MoSe2 to the pyridine ionic liquid aqueous solution is 1 mg: 1 to 1.2 mL, and the concentration of the pyridine ionic liquid aqueous solution is 0.001 to 0.01 mol / L.
[0012] Further specifying, the temperature of the ultrasonic liquid phase ablation is 20–30°C.
[0013] Further specified, the ultrasonic power of the ultrasonic liquid phase ablation is 275W, and the ultrasonic time is 6-8h.
[0014] Further specifying, the centrifugal washing includes two processes: low-speed centrifugal washing and high-speed centrifugal washing. The low-speed centrifugal washing is performed at a speed of 2500–3500 rpm for 5–10 min, with 2–3 centrifugal washes. The centrifugal washing solvent is a mixed solvent of water and ethanol. The upper dispersion after low-speed centrifugal washing is then subjected to high-speed centrifugal washing again at a speed of 10000–18000 rpm for 3–10 min. The centrifugal washing solvent is a mixed solvent of water and ethanol. The bottom precipitate is collected and washed at least 10 times with secondary water and at least 3 times with ethanol to remove residual ionic liquid. Finally, the washed precipitate is vacuum dried at 30–50 °C to obtain pure MoSe2 nanosheets.
[0015] Further specifying, the bulk material MoSe2 is in 1-dodecylpyridineisonicotinic acid [C 12MoSe2 nanosheets obtained by exfoliation from aqueous solution of [py][C6H4NO2] ionic liquid exhibit excellent two-dimensional sheet morphology characteristics, with an average lateral size of 1-4 μm, 80% of the nanosheet thickness concentrated in 1-2 nm, corresponding to 2-3 nanolayers, and all sheets are ultrathin nanostructures with ≤3 layers.
[0016] Further specifying, the bulk material MoSe2 is in 1-tetradecylpyridineisonicotinic acid [C 14 The MoSe2 nanosheets obtained by exfoliation from the aqueous solution of the py][C6H4NO2] ionic liquid have a lateral size of 1-2 μm, are thin sheets, and exhibit a clear 1-3 layer stacked structure. The lattice fringe spacing of the MoSe2 nanosheets is 0.67 nm, and they have a symmetrical distribution mode of single-crystal diffraction spots with hexagonal crystal system characteristics. The MoSe2 nanosheets have single-crystal properties and a yield as high as 37%.
[0017] Compared with existing technologies, this invention has the following advantages and beneficial effects: This invention utilizes the chain length of alkyl groups in pyridine-based ionic liquids to alter the interlayer spacing of the bulk material MoSe2. Ionic liquids with moderately long alkyl chains can smoothly penetrate the interlayer space of the bulk material, effectively expanding the interlayer spacing and effectively weakening the van der Waals forces. Furthermore, the C=OO ratio of the anions in the pyridine-based ionic liquids... - Lewis acid-base interactions exist between the functional groups and the bulk MoSe2 material layers. This interaction drives the pyridine ionic liquid to enter the interlayer of the bulk MoSe2 material, which is beneficial for the efficient preparation of MoSe2 nanosheets. In this invention, the addition of pyridine ionic liquid greatly promotes the dispersion of bulk MoSe2 material in aqueous solution, resulting in a MoSe2 nanosheet dispersion with ultra-high stability. Compared with traditional TMDs nanosheet preparation methods, this invention has advantages such as environmental friendliness, simple preparation process, and low-cost, large-scale, and high-quality preparation of few-layer MoSe2 nanosheets. The lateral dimensions of the nanosheets obtained by exfoliation in the pyridine ionic liquid aqueous solution are mostly distributed in the range of 0.6–2.2 μm. Through orthogonal experimental design, key parameters such as the concentration of the ionic liquid aqueous solution, the initial concentration of the bulk MoSe2 material, the ultrasonic time, and the ultrasonic power were systematically optimized. Under optimal conditions, the yield of MoSe2 nanosheets reached as high as 37%, and the proportion of nanosheets with a thickness of less than 2 nm reached as high as 80%. Attached Figure Description
[0018] Figure 1 The XRD patterns and Raman spectra of the bulk material MoSe2 in Examples 3-5 and the MoSe2 nanosheets prepared in pyridine-based ionic liquid aqueous solution are shown in comparison.
[0019] Figures 2a-2c Examples 3-5 are respectively in [C 16[py][C6H4NO2]、[C 14 [py][C6H4NO2]、[C 12 AFM and thickness statistics of MoSe2 nanosheets prepared in aqueous solution of [py][C6H4NO2] ionic liquid.
[0020] Figure 3 The images show a comparison of SEM images of the bulk material MoSe2 from Examples 3-5 and the MoSe2 nanosheets obtained by exfoliation in a pyridine-based ionic liquid aqueous solution system.
[0021] Figure 4 For Example 4 in [C 14 TEM, HR-TEM and SAED images of MoSe2 nanosheets prepared in aqueous solution of [py][C6H4NO2] ionic liquid.
[0022] Figure 5 For Example 4 in [C 14 XPS spectra of Mo3d and Se3d of MoSe2 nanosheets prepared in aqueous solution of [py][C6H4NO2] ionic liquid.
[0023] Figure 6 The bulk material MoSe2 in Example 4 and in [C 14 XRD pattern of MoSe2 nanosheets prepared in aqueous solution of [py][C6H4NO2] ionic liquid and magnified image of diffraction peaks corresponding to the (002) plane.
[0024] Figure 7 Example 4 is in MoSe2 / [C 14 [py][C6H4NO2]、[C 14 Comparison of FI-IR spectra of [py][C6H4NO2] and bulk material MoSe2. Detailed Implementation
[0025] The following examples further illustrate the above-described content of the present invention, but it should not be construed as limiting the scope of the subject matter of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention.
[0026] Example 1
[0027] Preparation of MoSe2 nanosheets in an aqueous solution of [C8py][C6H5NO2] ionic liquid
[0028] Step S1: Weigh 10 mg of block material MoSe2 and disperse it in 10 mL of prepared 0.01 mol / L [C8py][C6H5NO2] ionic liquid aqueous solution. Stir at room temperature for 10 min to make the block material evenly dispersed.
[0029] Step S2: Place the uniformly dispersed block material in a 20mL glass bottle and perform ultrasound with a probe for 6 hours. The ultrasound power is 275W and the ultrasound temperature is maintained at 25℃ to obtain a black suspension.
[0030] Step S3: Transfer the suspension obtained by sonication into a 5 mL centrifuge tube and centrifuge twice at 2000 rpm for 10 min each time. The collected supernatant is the MoSe2 nanosheet dispersion obtained by exfoliation.
[0031] Step S4: Centrifuge the obtained dispersion at 18000 rpm for 10 min. The precipitate after centrifugation is MoSe2 nanosheets. Then wash the nanosheets with deionized water more than ten times to remove residual ionic liquid [C8py][C6H5NO2]. Finally, wash with ethanol twice. Place the washed precipitate in a vacuum drying oven at 40℃ overnight to obtain relatively pure MoSe2 nanosheets.
[0032] Example 2
[0033] In [C] 10 Preparation of MoSe2 nanosheets in aqueous solution of [py][C6H5NO2] ionic liquid
[0034] Step S1: Weigh 10 mg of the block material MoSe2 and disperse it in 10 mL of a prepared 0.01 mol / L [C] solution. 10 In an aqueous solution of the ionic liquid [py][C6H5NO2], the block material was stirred at room temperature for 10 min to disperse it evenly.
[0035] Step S2: Place the uniformly dispersed block material in a 20mL glass bottle and perform ultrasound with a probe for 6 hours. The ultrasound power is 275W and the water bath temperature is maintained at 25℃ to obtain a black suspension.
[0036] Step S3: Transfer the suspension obtained by sonication into a 5 mL centrifuge tube and centrifuge twice at 2000 rpm for 10 min each time. The collected supernatant is the MoSe2 nanosheet dispersion obtained by exfoliation.
[0037] Step S4: Centrifuge the obtained dispersion at 18000 rpm for 10 min. The precipitate after centrifugation is MoSe2 nanosheets. Then wash the nanosheets with deionized water more than ten times to remove residual ionic liquid [C]. 10 [py][C6H5NO2], and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure MoSe2 nanosheets.
[0038] Example 3
[0039] In [C] 12 Preparation of MoSe2 nanosheets in aqueous solution of [py][C6H5NO2] ionic liquid
[0040] Step S1: Weigh 10 mg of the block material MoSe2 and disperse it in 10 mL of a prepared 0.012 mol / L [C] solution. 12 In an aqueous solution of the ionic liquid [py][C6H5NO2], the block material was stirred at room temperature for 10 min to disperse it evenly.
[0041] Step S2: Place the uniformly dispersed block material MoSe2 in a 20mL glass bottle and perform ultrasound with a probe. Set the ultrasound time to 6h, the ultrasound power to 275W, and the water bath ultrasound temperature to 25℃ to obtain a black suspension.
[0042] Step S3: Transfer the suspension obtained by sonication into a 5 mL centrifuge tube and centrifuge twice at 2000 rpm for 10 min each time. The collected supernatant is the MoSe2 nanosheet dispersion obtained by exfoliation.
[0043] Step S4: Centrifuge the obtained dispersion at 18000 rpm for 10 min. The precipitate after centrifugation is MoSe2 nanosheets. Then wash the nanosheets with deionized water more than ten times to remove residual ionic liquid [C]. 12 [py][C6H5NO2], and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure MoSe2 nanosheets.
[0044] Example 4
[0045] In [C] 14 Preparation of MoSe2 nanosheets in aqueous solution of [py][C6H5NO2] ionic liquid
[0046] Step S1: Weigh 10 mg of the block material MoSe2 and disperse it in 10 mL of a prepared 0.016 mol / L [C] solution. 14 In an aqueous solution of the ionic liquid [py][C6H5NO2], the block material was stirred at room temperature for 10 min to disperse it evenly.
[0047] Step S2: Place the uniformly dispersed block material MoSe2 in a 20mL glass bottle and perform ultrasound with a probe for 8 hours. The ultrasound power is 275W and the water bath temperature is maintained at 25℃ to obtain a black suspension.
[0048] Step S3: Transfer the suspension obtained by sonication into a 5 mL centrifuge tube and centrifuge twice at 2000 rpm for 10 min each time. The collected supernatant is the MoSe2 nanosheet dispersion obtained by exfoliation.
[0049] Step S4: Centrifuge the obtained dispersion at 18000 rpm for 10 min. The precipitate after centrifugation is MoSe2 nanosheets. Then wash the nanosheets with deionized water more than ten times to remove residual ionic liquid [C]. 14 [py][C6H5NO2], and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure MoSe2 nanosheets.
[0050] Example 5
[0051] In [C] 16 Preparation of MoSe2 nanosheets in aqueous solution of [py][C6H5NO2] ionic liquid
[0052] Step S1: Weigh 10 mg of the block material MoSe2 and disperse it in 10 mL of a prepared 0.002 mol / L [C] solution. 16 In an aqueous solution of [py][C6H5NO2], stir at room temperature for 10 minutes to disperse the blocky material evenly.
[0053] Step S2: Place the uniformly dispersed block material MoSe2 in a 20mL glass bottle and perform ultrasound with a probe. Set the ultrasound time to 6h, the ultrasound power to 275W, and the water bath ultrasound temperature to 25℃ to obtain a black suspension.
[0054] Step S3: Transfer the suspension obtained by sonication into a 5 mL centrifuge tube and centrifuge twice at 2000 rpm for 10 min each time. The collected supernatant is the MoSe2 nanosheet dispersion obtained by exfoliation.
[0055] Step S4: Centrifuge the obtained dispersion at 18000 rpm for 10 min. The precipitate after centrifugation is MoSe2 nanosheets. Then wash the nanosheets with deionized water more than ten times to remove residual ionic liquid [C]. 16 [py][C6H5NO2], and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure MoSe2 nanosheets.
[0056] Table 1 shows the optimization of the concentration of the ionic liquid aqueous solution, the initial concentration of the bulk MoSe2 material, the ultrasonic power, and the ultrasonic time using a three-variable, five-level orthogonal experimental method. Table 2 shows the yield of MoSe2 nanosheets and the concentration of the dispersion obtained under the optimal exfoliation conditions. The bulk MoSe2 material is shown in [C...]14 The highest yield of nanosheets, up to 37%, was obtained by exfoliation in aqueous solution of the py][C6H5NO2] ionic liquid.
[0057] Table 1
[0058]
[0059] Table 2
[0060]
[0061] Figure 1 The XRD patterns and Raman spectra of MoSe2 nanosheets prepared in pyridine-based ionic liquid solutions are compared with those of bulk MoSe2. Compared with bulk MoSe2, the intensity of the XRD diffraction peak on the (002) crystal plane is significantly reduced, indicating that the stacked layered structure undergoes significant thinning during exfoliation. Furthermore, the XRD diffraction peaks of the (004), (110), (103), (006), (105), and (008) crystal planes of the MoSe2 nanosheets are still clearly visible. Similar results have been observed in other ionic liquid aqueous solutions. These results indicate that in [C... 12 [py][C6H4NO2]、[C 14 [py][C6H4NO2]、[C 16 MoSe2 nanosheets were successfully prepared in an aqueous solution system of [C6H4NO2] ionic liquid. 14 Taking the exfoliated MoSe2 nanosheets in the [py][C6H4NO2] ionic liquid aqueous solution system as an example, it was found that compared with bulk materials, the out-of-plane characteristic vibrational peaks (A) of MoSe2 nanosheets are more pronounced. 1g From 249.7cm -1 The redshift reached 242.1 cm. -1 This directly confirms that the dimensionality of MoSe2 nanosheets is significantly reduced along the c-axis. Simultaneously, the MoSe2 nanosheets at 248.1 cm⁻¹... -1 out-of-plane vibration peak (A) 1g ) and 175.3cm -1 In-plane vibration peak (E) 1g The crystal structure of MoSe2 remains clearly discernible, indicating that it was completely preserved during the exfoliation process. Similar results were observed in other aqueous solutions of ionic liquids.
[0062] Figures 2a-2c They are respectively in [C 16 [py][C6H4NO2]、[C 14 [py][C6H4NO2] and [C 12A statistical graph of the AFM and thickness of MoSe2 nanosheets obtained in aqueous solution of [C6H4NO2] ionic liquid. The graph shows that in [C6H4NO2] ionic liquid... 12 MoSe2 nanosheets obtained in the [C6H4NO2] ionic liquid aqueous solution system exhibited excellent two-dimensional sheet morphology characteristics, with an average lateral size of 1–4 μm. 80% of the nanosheets had a thickness concentrated between 1–2 nm (corresponding to 2–3 nanolayers), and all sheets were ultrathin nanostructures with ≤3 layers. Further analysis of the thickness of 50 randomly selected nanosheets from each of the other three systems revealed that single-layer (<1 nm) nanosheets in [C6H4NO2] ionic liquid aqueous solution exhibited excellent two-dimensional sheet morphology characteristics, with an average lateral size of 1–4 μm. 80% of the nanosheets had a thickness concentrated between 1–2 nm (corresponding to 2–3 nanolayers), and all sheets were ultrathin nanostructures with ≤3 layers. 16 [py][C6H4NO2]、[C 14 [py][C6H4NO2]、[C 12 The percentages of py][C6H4NO2] ionic liquid in the aqueous solution system were 20%, 13%, and 19%, respectively. This indicates that the longer the alkyl chain on the cation of the pyridine ionic liquid, the higher the proportion of monolayer nanosheets prepared in the aqueous solution of the ionic liquid, which is more conducive to the production of monolayer nanosheets.
[0063] Figure 3 SEM images show bulk MoSe2 and exfoliated MoSe2 nanosheets. The images show that the bulk MoSe2 exhibits a regular cubic layered stacked structure, while the lateral dimensions and thickness are significantly reduced after ultrasonic exfoliation with an ionic liquid aqueous solution. [C] 14 MoSe2 nanosheets prepared in aqueous solution of [C6H4NO2] ionic liquid have a lateral size of 1–2 μm, exhibiting a thin sheet-like shape and significantly reduced thickness. 12 py][C6H4NO2] / [C 16 The sample prepared in aqueous solution of the py][C6H4NO2] ionic liquid is a few-layer sheet-like nanostructure (lateral dimension approximately 200–500 nm).
[0064] Figure 4 For in [C 14 TEM, HR-TEM, and SAED images of MoSe2 nanosheets prepared in aqueous solution of [C6H4NO2] ionic liquid. The images show that in [C6H4NO2] ionic liquid... 14 The MoSe2 nanosheets exfoliated in the [py][C6H4NO2] ionic liquid aqueous solution exhibit a clear 1-3 layer stacked structure, indicating that the bulk material MoSe2 has been successfully transformed into few-layer MoSe2 nanosheets through intercalation and exfoliation in the ionic liquid aqueous solution. Figure 4The HR-TEM image in (c) shows that the lattice fringe spacing of MoSe2 is 0.67 nm, which is highly consistent with the d-interval of the (002) crystal plane of monolayer MoSe2 (the theoretical value in the literature is 0.65 nm). Selected area electron diffraction analysis revealed a symmetrical distribution pattern of single-crystal diffraction spots with hexagonal crystal system characteristics, directly indicating that the prepared nanosheets possess single-crystal properties. Figure 4 (d) The combination of HR-TEM and SAED images further confirms the excellent crystal integrity and uniformity of the sheet-like structure of the nanosheets.
[0065] Figure 5 For in [C 14 XPS spectra of MoSe2 nanosheets prepared in aqueous solution of [py][C6H4NO2] ionic liquid. From this figure, it can be seen that Mo 3d 5 / 2 and Mo 3d 3 / 2 The characteristic binding energies are 228.7 eV and 231.8 eV, respectively, for Se 3d. 5 / 2 and Se3d 3 / 2 The characteristic binding energies were 54.2 eV and 54.9 eV, respectively. These XPS results indicate that the MoSe2 surface was not oxidized, and no defects or impurities (such as residual ionic liquid) were introduced during the exfoliation process. MoSe2 nanosheets obtained by exfoliation in other ionic liquid aqueous solutions were also not oxidized.
[0066] Figure 6 For bulk materials MoSe2 and in [C 14 The XRD pattern and magnified view of the diffraction peaks corresponding to the (002) plane of MoSe2 nanosheets prepared in the [C6H4NO2] ionic liquid aqueous solution system are shown in the figure. As can be seen from the figure, the intercalation significantly alters the crystallographic characteristics of MoSe2, resulting in a sharp decrease in the intensity of the characteristic diffraction peaks of the composite. Specifically, the (002) plane diffraction peak not only shows a significant increase in full width at half maximum (FWHM), but its peak position also shifts to a lower angle direction by 0.08°. This phenomenon is clearly shown in the magnified view, indicating that [C6H4NO2] ionic liquid... 14 The py][C6H4NO2] molecule successfully intercalates into the interlayer and induces lattice strain, leading to increased interlayer spacing and weakened interlayer forces.
[0067] Figure 7 MoSe2 / [C 14 [py][C6H4NO2]、[C 14 FI-IR spectra of [py][C6H4NO2] and bulk material MoSe2. The characteristic vibrational peaks of the ionic liquid in the complex show significant shifts, with the antisymmetric and symmetric stretching vibration peaks of -CH2 shifting from 2922 cm⁻¹ to [C6H4NO2]. -1 and 2853cm -1 Blue shifted to 2933cm -1 and 2869cm-1 And -C = OO - The antisymmetric and symmetric stretching vibration peaks are from 1600 cm⁻¹ -1 and 1370cm -1 Migration to 1616cm -1 and 1412cm -1 This result confirms that the C=OO in ionic liquid anions... - Strong Lewis acid-base interactions exist between the functional groups and the MoSe2 layers, which weaken the interlayer binding force of MoSe2 through intercalation effect, thereby driving its exfoliation process.
[0068] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are only illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from the scope of the principles of the present invention, and all such changes and modifications fall within the protection scope of the present invention.
Claims
1. A method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquids in aqueous solution, characterized in that... The specific steps are as follows: MoSe2 bulk material is placed in an aqueous solution of a pyridine-based ionic liquid for ultrasonic liquid-phase exfoliation using a probe. The dispersion is then centrifuged, washed, and dried to obtain MoSe2 nanosheets. The pyridine-based ionic liquid is 1-dodecylpyridineisonicotinic acid [C]. 12 [py][C6H5NO2], 1-Tetradecylpyridineisonicotinic acid [C 14 [py][C6H5NO2] or 1-hexadecylpyridineisonicotinic acid [C 16 [py][C6H5NO2]; The structural formula of the anion in the pyridine-based ionic liquid is: The structural formula of the cation in the pyridine-based ionic liquid is:
2. The method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution according to claim 1, characterized in that: The feeding ratio of the bulk material MoSe2 to the pyridine ionic liquid aqueous solution is 1 mg: 1 to 1.2 mL, and the concentration of the pyridine ionic liquid aqueous solution is 0.001 to 0.01 mol / L.
3. The method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution according to claim 1, characterized in that: The temperature for ultrasonic liquid phase ablation is 20–30°C.
4. The method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution according to claim 1, characterized in that: The ultrasonic power for the ultrasonic liquid phase ablation is 275W, and the ultrasonic time is 6-8 hours.
5. The method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution according to claim 1, characterized in that: The centrifugal washing process includes two steps: low-speed centrifugal washing and high-speed centrifugal washing. The low-speed centrifugal washing is performed at a speed of 2500–3500 rpm for 5–10 min, with 2–3 cycles of centrifugal washing. The washing solvent is a mixture of water and ethanol. The upper dispersion after low-speed centrifugal washing is then subjected to high-speed centrifugal washing again at a speed of 10000–18000 rpm for 3–10 min. The washing solvent is a mixture of water and ethanol. The bottom precipitate is collected and washed at least 10 times with water and at least 3 times with ethanol to remove residual ionic liquid. Finally, the washed precipitate is vacuum dried at 30–50 °C to obtain pure MoSe2 nanosheets.
6. The method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution according to claim 1, characterized in that: The bulk material MoSe2 in 1-dodecylpyridinium isonicotinic acid [C 12 MoSe2 nanosheets obtained by exfoliation from aqueous solution of [py][C6H4NO2] ionic liquid exhibit excellent two-dimensional sheet morphology characteristics, with an average lateral size of 1-4 μm, 80% of the nanosheet thickness concentrated in 1-2 nm, corresponding to 2-3 nanolayers, and all sheets are ultrathin nanostructures with ≤3 layers.
7. The method for liquid-phase exfoliation of MoSe2 nanosheets based on pyridine-based ionic liquid aqueous solution according to claim 1, characterized in that: The bulk material MoSe2 in 1-tetradecylpyridineisonicotinic acid [C 14 The MoSe2 nanosheets obtained by exfoliation from the aqueous solution of the py][C6H4NO2] ionic liquid have a lateral size of 1-2 μm, are thin sheets, and exhibit a clear 1-3 layer stacked structure. The lattice fringe spacing of the MoSe2 nanosheets is 0.67 nm, and they have a symmetrical distribution mode of single-crystal diffraction spots with hexagonal crystal system characteristics. The MoSe2 nanosheets have single-crystal properties and a yield as high as 37%.
Citation Information
Patent Citations
Liquid-phase peeling method for transition metal disulphide nanosheets
CN106966371A
A two-dimensional black phosphorus nanosheet and its liquid-phase exfoliation preparation method
CN107416784B